Status of White Sturgeon (Acipenser transmontanus Richardson, 1863) throughout the species range, threats to survival, and prognosis for the future. (December 2016) - Hildebrand, L. R.; Drauch Schreier, A.; Lepla, K.; McAdam, S. O.; McLellan, J.; Parsley, M. J.; Paragamian, V. L.; Young, S.P.
Summary: White Sturgeon, Acipenser transmontanus (WS), are distributed throughout three major river basins on the West Coast of North America: the Sacramento‐San Joaquin, Columbia, and Fraser River drainages. Considered the largest North American freshwater fish, some WS use estuarine habitat and make limited marine movements between river basins. Some populations are listed by the United States or Canada as threatened or endangered (upper Columbia River above Grand Coulee Dam; Kootenai River; lower, middle and, upper Fraser River and Nechako River), while others do not warrant federal listing at this time (Sacramento‐San Joaquin Rivers; Columbia River below Grand Coulee Dam; Snake River). Threats that impact WS throughout the species' range include fishing effects and habitat alteration and degradation. Several populations suffer from recruitment limitations or collapse due to high early life mortality associated with these threats. Efforts to preserve WS populations include annual monitoring, harvest restrictions, habitat restoration, and conservation aquaculture. This paper provides a review of current knowledge on WS life history, ecology, physiology, behavior, and genetics and presents the status of WS in each drainage. Ongoing management and conservation efforts and additional research needs are identified to address present and future risks to the species.